Alternativas para tratar lodos originados en sistemas de tratamiento de aguas residuales: una revisión - Cárdenas Torrado, Geraldine; Molina Pérez, Francisco José (Ingeniería, 2022)
Context: Research has shown the efficiency of various treatments for sludge. However, new alternatives have been presented which merit an updated review. That is why this work aims to carry out said update with regard to conventional and new techniques to treat sludge. Method: The article is based on a review of documents in various databases, first grouping the conventional alternatives and later the new ones, both consisting of alternatives of sludge thickening, stabilization, and dewatering techniques, and analyzing them based on economic, technical, and environmental criteria. Results: This study found that direct osmosis is one of the most promising alternatives in sludge thickening, supercritical water oxidation, and pyrolysis in stabilization and vacuum filtration during the dehydration of said byproducts. Conclusions: This article allowed an updated review of conventional and new alternatives for sludge treatment, observing that, both in thickening and stabilization, the new alternatives are highly efficient, whereas vacuum filtration, a conventional alternative, improved its performance through the use of modified flocculants, standing out in the dehydration of sludge. This is why more research is required which improve the current challenges and yields and inquire into the release of pollutants into the environment when using biosolids.